Start-up Costs, Taxes and Innovative Entrepreneurship - Pourya Darnihamedani; Joern Hendrich Block; Jolanda Hessels; Aram Simonyan (Tinbergen Institute, 2015)
Prior research suggests that start-up costs and taxes negatively influence entry into entrepreneurship. Yet, no distinction is made regarding the type of entrepreneurship, particularly innovative versus non-innovative entrepreneurship. Start-up costs, being one-off costs, may reduce the entry of entrepreneurs whose ideas are not very promising, thus increasing the proportion of innovative entrepreneurs. Taxes, being recurring costs, may reduce the prize of innovation and the profit from entrepreneurship, discouraging individuals with innovative business ideas from becoming entrepreneurs. Analyzing a dataset of 632,116 individuals, including 43,223 entrepreneurs from 53 countries, we can confirm our main predictions. Our paper contributes to the discussion on how governmental regulation costs and taxes influence innovative entrepreneurship and technological deve lopment.
Keywords: H24; H25; L26; L51; O31; 330; Innovative entrepreneurship; corporate taxes; personal income taxes; start-up costs; entrepreneurial profit